Behavioral evidence of a dissociation between voice gender categorization and phoneme categorization using auditory morphed stimuli - Pernet, Cyril R.; Belin, Pascal; Jones, Anna (Frontiers in Psychology, 2014)
Both voice gender and speech perception rely on neuronal populations located in the peri-sylvian areas. However, whilst functional imaging studies suggest a left versus right hemisphere and anterior versus posterior dissociation between voice and speech categorization, psycholinguistic studies on talker variability suggest that these two processes (voice and speech categorization) share common mechanisms. In this study, we investigated the categorical perception of voice gender (male vs. female) and phonemes (/pa/ vs. /ta/) using the same stimulus continua generated by morphing. This allowed the investigation of behavioural differences while controlling acoustic characteristics, since the same stimuli were used in both tasks. Despite a higher acoustic dissimilarity between items during the phoneme categorization task (a male and female voice producing the same phonemes) than the gender task (the same person producing 2 phonemes), results showed that speech information is being processed much faster than voice information. In addition, f0 or timbre equalization did not affect RT, which disagrees with the classical psycholinguistic models in which voice information is stripped away or normalized to access phonetic content. Also, despite similar response (percentages) and perceptual (d’) curves, a reverse correlation analysis on acoustic features revealed, as expected, that the formant frequencies of the consonant distinguished stimuli in the phoneme task, but that only the vowel formant frequencies distinguish stimuli in the gender task. The 2nd set of results thus also disagrees with models postulating that the same acoustic information is used for voice and speech. Altogether these results suggest that voice gender categorization and phoneme categorization are dissociated at an early stage on the basis of different enhanced acoustic features that are diagnostic to the task at hand.